Influence of environmental enrichment on sexual behavior and the process of learning and memory in a rat model of autism with valproic acid - Javik Dorantes-Barrios, C; Reyes-Meza, Verónica; Camacho-Candia, Josué A; Pfaus, James G; González-Flores, Oscar (Brain research, 2024)
Autism spectrum disorder (ASD) is a psychiatric disorder with severe behavioral consequences and no specific therapy. Its etiology is multifactorial, as it is caused by a complex interaction of genetic and environmental factors. In rats, prenatal exposure to the antiepileptic drug valproic acid (VPA) has been associated with an increased risk of autistic-like behaviors in offspring, including social behavior deficits, increased repetitive behaviors, and cognitive impairments. In addition, VPA-treated rats have shown altered sociosexual behaviors. However, the mechanisms underlying these alterations in reproductive processes in VPA-treated rats are not fully understood. Interestingly some abnormal behaviors in VPA autism models are improved by an enriched environment (EE). In the present study, we examined the effects of EE on memory performance and sexual behavior in male rats. We found that on postnatal day 90, EE reduced the time it took for both control and VPA-treated groups to find a hidden platform in the Morris water maze. On PND 100, prenatal exposure to VPA reduced total exploring time in object recognition tests. On PND 110, EE reduced mount and intromission latency and increased ejaculatory frequency in VPA-treated male rats. These results suggest that environmental stimuli significantly influence the onset of sexual behavior in VPA-treated male rats and that EE may be a potential tool for improving a variety of behavioral deficiencies in rodent models of autism.
Keywords: Animals; Autistic Disorder; Female; autistická porucha; Valproic Acid; ženské pohlaví; kyselina valproová; lidé; těhotenství; zpožděný efekt prenatální expozice; poruchy autistického spektra; Sexual Behavior; sexuální chování; Male; Prenatal Exposure Delayed Effects; krysa rodu Rattus; mužské pohlaví; zvířata; Pregnancy; Autism Spectrum Disorder; Rats; Humans